2009
DOI: 10.1111/j.1365-2230.2008.02900.x
|View full text |Cite
|
Sign up to set email alerts
|

Lichen planus pemphigoides associated with Chinese herbs

Abstract: We report a 62-year-old Chinese woman with a 2-year history of lichen planus presenting with extensive violaceous maculopapules and plaques 1 week after taking an oral preparation of Chinese herbs. The patient developed vesiculobullous skin lesions 7 weeks later. Histopathological examination showed subepidermal blisters and adjacent bandlike lymphocytic infiltration. Direct immunofluorescence revealed linear deposits of IgG and C3 along the basement membrane zone. Indirect immunofluorescence showed IgG antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
1
7
0
3
Order By: Relevance
“…Circulating antibodies against the BP 180 antigen have been detected in most cases of LPP where molecular studies have been performed 2–8 . Reactivity with proteins of 130, 200, 230 and 240 kDa has also been reported 3,4,8,9 .…”
mentioning
confidence: 98%
“…Circulating antibodies against the BP 180 antigen have been detected in most cases of LPP where molecular studies have been performed 2–8 . Reactivity with proteins of 130, 200, 230 and 240 kDa has also been reported 3,4,8,9 .…”
mentioning
confidence: 98%
“…Olgumuzda indirekt immünofloresan ve immünoblotting incelemeler yapılamamış olmasına rağmen klinik, histopatolojik ve direkt immünofloresan bulgular LPP ile uyumludur. Genellikle idiyopatik olmakla birlikte literatürde hepatit B virüsü infeksiyonu, maliniteler, dar band UVB, PUVA ve bazı ilaçlarla ilişkili olarak ortaya çıkan LPP olguları bildirilmiştir [5][6][7][8][9][10][11][12][13][14][15][16] . LPP oluşumunda suçlanan ilaçlar arasında sinnarizin, ramipril, kaptopril, simvastatin, furusemid, parasetamol, ibuprofen ve paroksetin bulunmaktadır [7][8][9][10][11][12][13][14][15][16] .…”
Section: Discussionunclassified
“…Likenoid ilaç erupsiyonlarında ilacı kestikten sonra spontan gerileme izlenebilmekte ve bu durum tanıyı destekler bir bulgu olsa da, bizim olgumuzda lezyonların yaygınlığı ve şiddeti nedeniyle sistemik tedavi başlanması gerekmiştir. Çünkü ilaç kesilse bile mevcut tablonun ilacın kesilmesini takiben ancak birkaç hafta ile birkaç ay içinde düzelebileceği bildirilmektedir [8][9][10][11][12][13][14][15] . Suçlanan ilaca hastanın tekrar maruz bırakılması ise tehlikeli sonuçlar doğurabileceğinden genellikle önerilmemektedir 17 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Xu et al [31] reported a patient who developed lichen planus pemphigoides a few weeks after taking an oral preparation of Chinese herbs. The patient did not experience any relapse after she stopped taking the herbs.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%